Cell-cycle regulatory proteins in human wound healing - Bártková, Jiřina; Gron, B; Dabelsteen, E; Bártek, Jiří (Archives of oral biology, 2003)
Proper healing of mucosal wounds requires careful orchestration of epithelial cell migration and proliferation. To elucidate the molecular basis of the lack of cellular proliferation in the migrating 'epithelial tongue' during the re-epithelialization of oral mucosal wounds, the expression of cell-cycle regulators critical for G(1)-phase progression and S-phase entry was here analysed immunohistochemically. Compared to normal human mucosa, epithelia migrating to cover 2- or 3-day-old wounds made either in vivo or in an organotypic cell culture all showed loss of the proliferation marker Ki67 and cyclins D(1) and A, and reduced expression of cyclins D(3) and E, the cyclin D-dependent kinase 4 (CDK4), the MCM7 component of DNA replication origin complexes and the retinoblastoma protein pRb. Among the CDK inhibitors (CKIs), p16ink4a and p21Cip1 were moderately increased and decreased, respectively, whereas the abundance of most of the CKIs, including p27Kip1, p57Kip2, p15ink4b and p18ink4c, was relatively maintained in the migrating epithelial tongue. These data indicate that downmodulation of several G(1)/S-phase cyclins and a relative excess of CKIs may cooperate to ensure the quiescent state of migrating keratinocytes during wound healing.
Keywords: epitelové buňky; G1 fáze; Epithelial Cells; Adult; dospělí; Cyclins; Cell Movement; proteiny buněčného cyklu; lidé; Wound Healing; Humans; S fáze; pohyb buněk; S Phase; G1 Phase; ústní sliznice; Cell Cycle Proteins; cykliny; Mouth Mucosa; hojení ran